2017
DOI: 10.1021/acs.langmuir.7b03019
|View full text |Cite
|
Sign up to set email alerts
|

Homogenous Dispersion of MoS2 Nanosheets in Polyindole Matrix at Air–Water Interface Assisted by Langmuir Technique

Abstract: Two-dimensional (2D) inorganic layered materials when embedded in organic polymer matrix exhibit exotic properties that are grabbing contemporary attention for various applications. Here, nanosheet morphology of molybdenum disufide (MoS) synthesized via one-pot facile hydrothermal reaction are exfoliated in benign aqueous medium in the presence of indole to obtain a stable dispersion. These exfoliated nanosheets then act as host to template the controlled polymerization of indole. The preassembled MoS-polyindo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Peaks at 254 nm originates from n-π* transition, whereas peaks positioned at 325 nm and 388 nm are due to the π-π* transition. Moreover, absorption peak at 428 nm and 505 nm arises due to polaronic transition in PIN [ 41 , 42 ]. Compared to indole UV-Vis spectrum as in the literature, the presence of more peaks with their shift towards the longer wavelength (bathochromic shift) in the spectra of PIN provides the evidence of higher extent of π-electronic conjugation in polymer.…”
Section: Resultsmentioning
confidence: 99%
“…Peaks at 254 nm originates from n-π* transition, whereas peaks positioned at 325 nm and 388 nm are due to the π-π* transition. Moreover, absorption peak at 428 nm and 505 nm arises due to polaronic transition in PIN [ 41 , 42 ]. Compared to indole UV-Vis spectrum as in the literature, the presence of more peaks with their shift towards the longer wavelength (bathochromic shift) in the spectra of PIN provides the evidence of higher extent of π-electronic conjugation in polymer.…”
Section: Resultsmentioning
confidence: 99%
“…Lots of efforts have been given to investigate different kinds of molecular aggregate formed onto LB films [37, 38, 39, 40, 41]. It has been shown that this technique is very suitable for preparation of different supramolecular aggregates, where the properties of such aggregates can be tuned by optimizing various parameters during film formation [83, 84].…”
Section: Main Textmentioning
confidence: 99%
“…The Langmuir-Blodgett (LB) technique has been widely used for nearly a century to deposit large-area molecular and particular monolayers onto a variety of substrates [28,29]. In addition, the LB technique has been used to obtain solid films of molybdenum disulfide (MoS 2 ) [30], and metal nanoparticles [20,31]. However, surface roughness of these films affects their optical properties [32,33].…”
Section: Introductionmentioning
confidence: 99%